FACTORS CONDITING THE FORMATION OF THE ARMENIAN DIASPORA IN GEORGIA - Omarov, V.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article analyzes the purposeful resettlement of Armenians in the Russian Empire in Georgia and the armenization of the region. The changes in the demographic situation in Georgia and their targeted growth after the revision of the Armenians in Turkey and Iran in Samtskhe-Javakheti, Kvemo-Kartli, and the province of Tbilisi are studied. In the 19th century, Russia put an end to the independence of Georgia (Kartli-Kakheti). After that, the Armenians were purposefully settled in Georgia. Information of a scientific, political and economic nature related to the demographic processes of Armenians in Georgia is very significant. They are of both scientific and practical importance. In this article, the external and internal factors of the resettlement of Armenians in Georgia, the stages of migration from ancient times to the present day, including economic, political and military aspects, were studied from a scientific point of view. For modern Georgia, the study of this problem is of great importance from a scientific, theoretical, practical and political point of view.